2021
DOI: 10.3389/ffgc.2021.620450
|View full text |Cite
|
Sign up to set email alerts
|

Older Eastern White Pine Trees and Stands Accumulate Carbon for Many Decades and Maximize Cumulative Carbon

Abstract: Pre-settlement New England was heavily forested, with trees exceeding 2 m in diameter. The forests have regrown since farm abandonment, representing what is arguably the most successful regional reforestation on record and identified recently in the “Global Safety Net.” Temperate “old-growth” forest and remnant stands demonstrate that native tree species can live several hundred years and continue to add to forest biomass and structural and ecological complexity. Forests globally are an essential natural clima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
(102 reference statements)
0
9
0
Order By: Relevance
“…The term "even-aged" can evoke images of a tree farm or a plantation, but natural forests do not have such a uniform structure, particularly those older than 60-80 years. Although 60-80 year old trees may be termed "mature, " or almost "overmature, " they are at far less than half their natural lifespan and likely at far less than 20% of their potential carbon accumulation (Thompson et al, 2009;Leverett et al, 2021). Most important, forests that are relatively even-aged will transition on naturally toward old-growth and uneven-aged condition if simply left alone (Gunn et al, 2014;Catanzaro and D'Amato, 2019).…”
Section: Rationale For Forest-clearing: Reduce the Prevalence Of "Mat...mentioning
confidence: 99%
See 2 more Smart Citations
“…The term "even-aged" can evoke images of a tree farm or a plantation, but natural forests do not have such a uniform structure, particularly those older than 60-80 years. Although 60-80 year old trees may be termed "mature, " or almost "overmature, " they are at far less than half their natural lifespan and likely at far less than 20% of their potential carbon accumulation (Thompson et al, 2009;Leverett et al, 2021). Most important, forests that are relatively even-aged will transition on naturally toward old-growth and uneven-aged condition if simply left alone (Gunn et al, 2014;Catanzaro and D'Amato, 2019).…”
Section: Rationale For Forest-clearing: Reduce the Prevalence Of "Mat...mentioning
confidence: 99%
“…Some studies suggest that younger forests between 30 and 70 years (Catanzaro and D'Amato, 2019) or 40-80 years (Leverett et al, 2021) can sequester carbon at a faster rate than mature or old-growth forests. Other analyses indicate that lands reserved from logging in the Northeast have net carbon sequestration rates that are roughly 33% higher than in logged forests and are projected to sequester more carbon over the next 150 years (Brown et al, 2018).…”
Section: Impacts On the Atmospherementioning
confidence: 99%
See 1 more Smart Citation
“…The age and height of a tree have shown a moderately good relationship and a considerable impact on CS. Leverett et al [47] reported that large trees had dominance in accumulating carbon and aged trees had a high accumulation rate of carbon. Matured and aged trees showed high values for CS along with the R 2 0 .99 for basal area and 0.60 for height [48].…”
Section: Carbon Sequestration and Characteristics Of Treesmentioning
confidence: 99%
“…Furthermore, some outputs (e.g., specialty products, such as poles or pilings, or maximizing carbon to be sequestered under contracts) may not be optimized by families selected for maximal early volume growth and short rotations. As an example, a growing body of evidence suggests significant carbon accumulation in older trees and stands that could alter strategies (much longer rotations) for using forests to sequester atmospheric carbon dioxide (e.g., Carey et al, 2001;Luyssaert et al, 2008;Stephenson et al, 2014;Sillett et al, 2019;Leverett et al, 2021).…”
Section: Introductionmentioning
confidence: 99%